Fatal Liver and Bone Marrow Toxicity by Combination Treatment of Dichloroacetate and Artesunate in a Glioblastoma Multiforme Patient: Case Report and Review of the Literature - Uhl, Martin; Schwab, Stefan; Efferth, Thomas (Frontiers in Oncology, 2016)
A 52 year-old male patient was treated with standard radiochemotherapy with temozolomide for glioblastoma multiforme. After worsening of his clinical condition, further tumor specific treatment was unlikely to be successful, and the patient seeked help from an alternative practitioner that administered a combination of dichloroacetate (DCA) and artesunate (ART). A few days later, the patient showed clinical and laboratory signs of liver damage and bone marrow toxicity (leukopenia, thrombocytopenia). Beside successful restoration of laboratory parameters upon symptomatic treatment the patient died 10 days after the infusion. DCA bears a well-documented hepatotoxic risk, while ART can be considered as safe concerning hepatotoxicity. Bone marrow toxicity can appear as reduced reticulocyte counts and disturbed erythropoiesis. It can be speculated that the simultaneous use of both drugs caused liver injury and bone marrow toxicity. The compassionate use of DCA/ARTcombination therapy outside of clinical trials cannot be recommended for GBM treatment.